Traces of Ato as a Judicial Institution in the Lupon of Talubin, Bontoc, Mt. Province - Alexander G. Killip Jr. (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2021)
Ato shows the existence of the indigenous political institution in the Cordillera specifically in Mt. Province that reflects the cultural patterns, political processes, and assumptions of rights of the community based on their customary laws that allow the indigenous people to achieve meaningful self-determination. The researcher wanted to determine and understand the traces of ato as a judicial institution in the Lupon through its public administration and judicial practices. The researcher made use of qualitative approach and descriptive design to understand the perceptions and beliefs of the Lupon members conveyed through their personal belief systems and knowledge on the customary laws which are currently being implemented in the community. Five (5) members of Lupon and three (3) barangay officials discussed the existing judicial and administrative practices of the Lupon. The study found out that the traces of ato as a judicial institution in the Lupon focus on the public administration practices that involve the processes of implementing and evaluating of policies such as the review on the ordinance by the barangay captain, posting of ordinance in the barangay hall and the house-to-house information dissemination by the tanods. On the other hand, there is no standardized tool in evaluating the policies being implemented, but the effectivity of the lupon is evaluated through the observation of the barangay captain. The judicial practices in the Lupon include conflict resolutions and imposition of sanctions. The judicial practices on conflict resolution in the Lupon follow a series of trial procedures; first one is the private mediation process of the barangay mediation council that involves only the barangay officers and the conflicting parties; and, the second one is the public trial of the conflict through arbitration by the Lupon members. The judicial practices on imposing sanctions include fine such as money, personal belongings, property, or livestock and community service. Overall, the use of customary laws on deciding cases in the Lupon are highly accepted by the people which make the role of the elders of the community as members of the Lupon highly significant.